Enhancement of the Coercive Field and Exchange Bias Effect in Fe3GeTe2/MnPX3 (X = S and Se) van der Waals Heterostructures - Dai, Hongwei; Cheng, Hui; Cai, Menghao; Hao, Qinghua; Xing, Yuntong; Chen, Hongjing; Chen, Xiaodie; Wang, Xia; Han, Jun-Bo (ACS applied materials & interfaces, 2021)
Fe3GeTe2/MnPS3 and Fe3GeTe2/MnPSe3 van der Waals heterostructures were fabricated by mechanical exfoliation. Via the magneto-optical Kerr effect and reflected magnetic circular dichroism measurements, we have observed nearly three times enhancement of the coercive field, improvement of Curie temperature, and exchange bias effect in both heterostructures. These observations may provide new insights into the emergent heterostructure devices between itinerant ferromagnets and metal thio- and selenophosphates for both applied and fundamental research studies in magnetic correlations.